Asymtomatic carriage of Neisseria meningitidis and Neisseria lactamica in relation to Streptococcus pneumoniae and Haemophilus influenzae colonization in healthy children: Apropos of 1400 children sampled - (:unkn) unknown (KLUWER ACADEMIC PUBL, 2001)
Meningococcal disease is one of the most important causes of morbidity and mortality among children in many parts of the world. Main reservoir of carriage and site of meningococcal dissemination appears to be the upper respiratory tract. Colonization of Neisseria meningitidis and lactamica and factors affecting this carriage were determined in a group of healthy children aged 0-10 years. Meningococcus and N. lactamica carriage were detected in 17 (1.23%) and 245 (17.7%) of 1382 subjects, respectively. Number (%) of serogroups for meningococci was 1 (6), 5 (29), 0 (0), 1 (6), 1 (6), and 9 (53) for A, B, C, D, W135, and Y, respectively. Having more than three household members, elementary school attendance, pharyngeal carriage of Streptococcus pneumoniae and Haemophilus influenzae were associated with carriage of meningococci, whereas age less than 24-month was associated with carriage of N. lactamica. There was a reverse carriage rate between N. meningitidis and N. lactamica by age which may suggest a possible protective role of N. lactamica against meningococcal colonization among pre-school children.
Keywords: children; epidemiology; Neisseria lactamica; Neisseria meningitides; MENINGOCOCCAL DISEASE; INFANTS